2021
DOI: 10.46281/ijfb.v5i1.963
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges of Financial Management Practices in Islamic Financial Institutions: Empirical Evidence From Bangladesh

Abstract: Studies suggest several issues and challenges of financial management practices in Islamic banks and insurance companies and Islamic non-bank financial institutions (INBFIs) in Bangladesh. The purpose of the research is to examine the issues and challenges of Islamic Financial Management (IFM) from an empirical perspective. The study relies on a structured questionnaire survey in prominent Islamic financial institutions (IFIs) of Bangladesh for achieving its objective. After confirming data reliability based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The study has addressed the concerns of all stakeholders in the money market as to the practical impact of monetary policy on economic development and the determinants of monetary policy. The study has identified the seven significant determinants that influence the monetary policy of Bangladesh Bank, such as the price risk factor, the factor of market operations, political and economic factors (Farooq et al, 2023;Dogru et al, 2019;Işık et al, 2017;Işık, 2015Işık, , 2013, governance factors, SDG factors (Dam et al, 2023;Han et al, 2023), fiscal and risk factors (Işık et al, 2023a(Işık et al, , 2023b, and factors of price stability and market liquidity (Islam et al, 2023a, Sarıgul et al, 2023Singh, 2022). By statistical analysis, these are the determinants that substantially impact monetary policy.…”
Section: Discussionmentioning
confidence: 99%
“…The study has addressed the concerns of all stakeholders in the money market as to the practical impact of monetary policy on economic development and the determinants of monetary policy. The study has identified the seven significant determinants that influence the monetary policy of Bangladesh Bank, such as the price risk factor, the factor of market operations, political and economic factors (Farooq et al, 2023;Dogru et al, 2019;Işık et al, 2017;Işık, 2015Işık, , 2013, governance factors, SDG factors (Dam et al, 2023;Han et al, 2023), fiscal and risk factors (Işık et al, 2023a(Işık et al, , 2023b, and factors of price stability and market liquidity (Islam et al, 2023a, Sarıgul et al, 2023Singh, 2022). By statistical analysis, these are the determinants that substantially impact monetary policy.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the literature review highlights the evolving discourse on financial literacy within financial institutions and the importance of bridging gaps in existing research. By situating this paper within the broader literature, we lay the foundation for a critical analysis of financial literacy in Bangladesh's financial institutions, addressing unsolved issues and contributing to the ongoing dialogue in this vital field of study (Islam, 2015;Islam, 2016a;Islam, 2016b;Islam, 2016d;Islam, 2016e;Islam, 2016f;Islam, 2016g;Islam, 2016h;Islam, 2016i;Islam & Salma, 2016a;Islam & Salma, 2016b;;Islam & Salma, 2016c;Islam & Barghouthi, 2017a;Islam & Barghouthi, 2017b;Islam & Barghouthi, 2017c;Islam & Barghouthi, 2017a. ;Islam & Barghouthi, 2017b.…”
Section: Literature Reviewmentioning
confidence: 99%